Health as a rich people’s game through the lens of work and income - Wen-Jui Han; Marc A. Scott; Nora Tang (BMC Public Health)
Abstract Background The growing reliance on precarious employment —work that is uncertain, insecure, and unstable —has transformed work for many from a resource to a vulnerability for health and well-being. Methods Using longitudinal data from the NLSY79 cohort (n ≈ 6,666) in the United States, we focused on two social determinants of health (SDOH), work and family income. We examine work schedule and income patterns between ages 22 and 49, explicitly building upon the life course lens to answer how such patterns before age 50 may shape future health outcomes at age 50. We used sequence analysis to categorize work and family income trajectories and multivariate regression to examine the relationship between work and family income trajectories on health at age 50. Results Our sequence analysis reveals four diverse work clusters ranging from stable standard daytime hours to volatile work patterns (e.g., not working, working evening or night hours, or variable hours) and four family income clusters ranging from upward mobility to persistent low-income patterns. Our multivariate regression suggests a strong income gradient in health, which plays a critical role in cushioning the otherwise adverse effects on health from volatile work patterns. In contrast, limited and volatile income exacerbates the negative effects of volatile work patterns on health. These adverse associations were particularly pronounced for females. Conclusions Taken together, our results demonstrate a strong income gradient in health that may be moderated by diverse work patterns, with significant implications for how work and income as SDOH factors play critical roles in shaping intergenerational poverty and inequality. Clinical trial number Not applicable.